Elmer and the rainbow [Elmer a dúha anglicky] - McKee, David (Andersen, 2009)
Elmer is sad when he discovers that the rainbow has lost its colours. He wants to help, but what will happen to him if he gives the rainbow his own colours? Will he lose them for ever? A classic story book about sharing and giving.